Der Arzt als „Verwalter des Rassengutes“? Eugenische Eheberatung in der deutschen und ungarischen Gesetzgebung bis 1945 - Abram, Helen Ahlke (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2022)
Throughout the first half of the 20th century, people were encouraged to choose their spouses based on heredity, race, and health in order to rid the “racial corpus” of “inferior” genetic material and to strengthen the genetic material of future generations. In the course of the eugenic and racial-hygienic discourse in Germany and Hungary, as well as in many other European countries and the USA, legal measures such as the compulsory exchange of health certificates before marriage, accompanied by bans on “unhealthy” or “inferior” marriages, were discussed by population policy. Subsequently, various pieces of legislation were passed that mandated marriage counselling as a basis for further eugenic measures, both selection and promotion. Starting on a voluntary basis, marriage counselling became compulsory in Germany from 1933 and in Hungary from 1941. The following article first looks at the different stages of legislations before discussing the differences and similarities between the German and Hungarian laws. The focus is on the question of whether doctors were used in both countries as “administrators of the hereditary property” and whether it is possible to speak of a mutual influence of the legislation. The legal comparison reveals that the legislations differed considerably in essential points.